Предпринимательство и механизмы дифференциации размеров успешной деятельности предпринимательских фирм - Elena Vasilyevna Romanenko; Vitaly Vasilyevich Biryukov (Вестник СибАДИ)
The development of the theory of entrepreneurship and differentiation of the dimensions of entrepreneurial firms are considered in the article . The refined methodology based on the formation of multilevel system of values to solve problems in the study of the influence of cultural values on goals and motives of entrepreneurship, as well as on the construction of relations of internal and external environment is presented . The integrative and dynamic approach to the analysis of entrepreneurial firms, causes and factors of formation of boundary conditions for their success is offered .